Study on Maintenance of Medical Equipment and Challenges Faced By Health Care Technology Management System: Strategies for Effective Medical Equipment Management (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Based on the research done in this study on how to manage medical equipment, it wasdiscovered that hospitals lack a complete and codified strategy for how to manage medical equipment,resulting in a waste of material and equipment capital for the organization. When there is no planningand control system in place for inventory, purchasing, and maintenance of medical equipment, severaldifficulties arise, including the buildup and depreciation of equipment, as well as the inability to providethese facilities in crucial situations. It is advised that strategies be developed to replace equipment incritical situations (such as abrupt failure) based on the kind of equipment and the cost of replacement,as well as the equipment's vitality. There are protocols in place to verify the safety of medical equipmentat several times, including before it is used on a patient, during a preventive maintenance programme,and after regular and significant repairs, all of which assist the hospital in planning and maintainingappropriate medical equipment